STRETCHING FLOWS WITH GENERAL SLIP BOUNDARY CONDITION - SAJID, M.; ALI, N.; ABBAS, Z.; JAVED, T. (International journal of modern physics. B, Condensed matter physics, statistical physics, applied physics, 2010)
General slip boundary condition is used to solve the viscous incompressible flows induced by a stretching sheet. These flow problems corresponds to the planar and axisymmetric stretching. A similarity solution is developed by shooting method using Runge–Kutta algorithm. The results are graphically displayed and discussed under the influence of slip parameter and critical shear rate. The comparison of stretching flow problem subject to Navier's boundary condition in the planar case is made with the available numerical results in the literature.